Construction of Full‐Spectrum‐Response Bi3O4Br:Er3+@Bi2O3‐x S‐Scheme Heterojunction With [Bi─O] Tetrahedral Sharing by Integrated Upconversion and Photothermal Effect Toward Optimized Photocatalytic Performance - Zhifeng Li; Liang Xu; Zhaoyi Yin; Junhao Ma; Xiaoyi Dong; Shangyong Wang; Zhiguo Song; Jianbei Qiu; Yongjin Li (Advanced Science)
Abstract Designing and optimizing photocatalysts to maximize the use of sunlight and achieve fast charge transport remains a goal of photocatalysis technology. Herein, a full‐spectrum‐response Bi3O4Br:Er3+@Bi2O3‐x core–shell S‐scheme heterojunction is designed with [Bi─O] tetrahedral sharing using upconversion (UC) functionality, photothermal effects, and interfacial engineering. The UC function of Er3+ and plasmon resonance effect of Bi2O3‐x greatly improves the utilization of sunlight. The equivalent layer structure of Bi3O4Br and Bi2O3‐x facilitates the construction of high‐quality S‐scheme heterojunction interfaces with close atomic‐level contact obtained from the [Bi─O] tetrahedral sharing and the resulting Bi3O4Br:Er3+@Bi2O3‐x core–shell morphology, enabled efficient charge transfer. Furthermore, localized temperature increase, induced by photothermal effects, enhanced the chemical reaction kinetics. Benefiting from the distinctive construction, the Bi3O4Br:Er3+@Bi2O3‐x heterojunctions exhibit excellent performance in the photocatalytic degradation of bisphenol A that is 2.40 times and 4.98 times greater than that of Bi3O4Br:Er3+ alone under full‐spectrum light irradiation and near‐infrared light irradiation, respectively. This work offers an innovative perspective for the design and fabrication of full‐spectrum‐response S‐scheme heterojunction photocatalysts with efficient solar energy utilization based on high quality interfaces, UC functionality, and the photothermal effect.